Public Awareness of Cancer Risk Factors and Symptoms: A Population-Based Assessment - Deshmukh, Asawari; Deshmukh, Sanika (Journal of Contemporary Medical Practice, 2025)
Background: The most prevalent malignancy is breast cancer (BC). BC was the cause of 10.6% of deaths in India and 13.5% of all cancer diagnoses, according to Globocan 2020. In this study, female patients in an urban private clinic in Central India were asked to rate their awareness and knowledge of breast cancer risk factors, symptoms, and screening procedures. Materials & Methods: A cross - sectional survey was conducted from July to December 2022 on a sample of 75 participants at an Urban private clinic in Central India. Results: Out of 75 participants in the study, 50 (66.6%) were unaware of any risk factors for breast cancer, which is the majority. Only 6 (8%), 4 (5.2%), and 3 (4%) recognised that having a first child after the age of 30 was a risk factor for breast cancer, as well as the family history of the disease. Three (4%) also knew that having a late menopause was a risk factor. The majority of subjects, 64 in total (85.3%), were unaware of any breast cancer symptoms. Three respondents (40%) knew all the symptoms of breast cancer, four subjects (40%) knew about painless lumps in the breast or armpit as a symptom, and two individuals (2.6%) knew about changes in the size, shape, or colour of the breast as a symptom. Similar to this, 6 (8%) of the individuals knew about mammography, while 60 (80%) of the subjects had no knowledge of any procedure. While only 2 (2.6%) of the individuals were aware of self - breast examination, 5 (6.6%) of the subjects were aware of all screening and detection strategies for breast cancer. Conclusion: Participants in the current study had extremely limited understanding of risk factors, symptoms, and screening and preventative techniques. Programmes to increase public awareness are desperately needed.